Modified montmorillonite filler based on phytic acid and cerium ions and water-borne epoxy resin anticorrosive coating
By using phenolic and cerium ion modified montmorillonite fillers in aqueous epoxy coatings, a coordinated protection mechanism is formed, which solves the problems of poor density and insufficient corrosion resistance of the aqueous epoxy coatings, and significantly improves corrosion resistance and resistance. Corrosiveness extends the service life of metal substrates.
Patent Information
- Application Number
- CN202411561376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing water-based epoxy coatings have poor density and cannot achieve long-term service effect, so they cannot effectively protect the corrosion of metal substrates in the marine environment.
Modified montmorillonite filler based on phytic acid and cerium ions is used to combine with aqueous epoxy resin, and montmorillonite is modified through cerium ions and phytic acid functional groups to form a coordinated protection mechanism to improve the anticorrosion performance of the coating.
It significantly improves the density and corrosion resistance of the aqueous epoxy coating, reduces the corrosion current density, and extends the service life of the metal substrate.
Smart Images

Figure CN119264716A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterborne epoxy resin anticorrosion coatings, and in particular to a modified montmorillonite filler based on phytic acid and cerium ions and a waterborne epoxy resin anticorrosion coating, wherein the coating can be applied to the protection of metal substrate corrosion caused by chloride ions in a marine environment. Background Art
[0002] As a spontaneously corroding substance, metal has an astonishing annual loss. The consumption of metal materials in service in the marine environment is even more innumerable. The fundamental reason is that the chloride ions in seawater will constantly contact the metal and cause corrosion. Compared with the service life of metal in a dry environment, the service life of metal in the marine environment is shorter, so more comprehensive protection is needed.
[0003] Epoxy resin has attracted attention as a material that can isolate metal from the external environment, but it will volatilize toxic substances during the drying and curing process, and is an environmentally unfriendly material. Water-based epoxy resin has attracted attention due to its own environmentally friendly properties, but water-based epoxy resin will inevitably have micropores and cracks during the preparation process, which greatly reduces the long-term protection of water-based epoxy coatings for metals. In order to meet the market's higher requirements for water-based epoxy coatings, how to improve the density and long-term service of water-based epoxy coatings is currently a key issue, and research on metal anti-corrosion coatings should be further followed up. Summary of the invention
[0004] In view of the shortcomings of the prior art water-based epoxy coatings such as poor density and inability to achieve long-term service effects, the purpose of the present invention is to provide a modified montmorillonite filler based on phytic acid and cerium ions and a water-based epoxy resin anti-corrosion coating. The prepared modified montmorillonite filler based on phytic acid and cerium ions can improve the anti-corrosion effect of the water-based epoxy resin anti-corrosion coating when used.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A modified montmorillonite filler based on phytic acid and cerium ions is formed by taking montmorillonite as a carrier and loading cerium ions and phytic acid functional groups on the carrier.
[0007] The preparation process of the modified montmorillonite filler (MMT-Ce-PA) comprises the following steps:
[0008] (1) using montmorillonite as a raw material to prepare a montmorillonite dispersion (MMT dispersion);
[0009] (2) Add Ce(NO) to the montmorillonite dispersion in step (1) 3 ) 3 6H 2O, and the reaction is complete under constant temperature of 60-80℃ and magnetic stirring;
[0010] (3) adding a phytic acid (PA) solution having a concentration of 65-75 wt.% to the material obtained after the reaction in step (2), and then gradually adding a NaOH solution to adjust the pH value of the solution to 8-8.5, and stirring with a magnetic stirrer until the reaction is complete to obtain an MMT-Ce-PA mixed solution;
[0011] (4) using a centrifuge to remove unreacted substances in the MMT-Ce-PA mixed solution, and washing with water to obtain a MMT-Ce-PA mud precipitate; the mud precipitate is dried to obtain the modified montmorillonite filler (MMT-Ce-PA), which is then sealed and stored.
[0012] In the above step (1), the preparation process of the montmorillonite dispersion (MMT dispersion) is: 0.1-1g of montmorillonite (MMT) is uniformly dispersed in 100ml of deionized water by ultrasonic dispersion method, ultrasonic dispersion is performed for 15-20 minutes, and then the montmorillonite dispersion (MMT dispersion) is uniformly dispersed under magnetic stirring conditions, and the magnetic stirring process is stirred at room temperature for 1-3h.
[0013] In the above step (3), the concentration of the NaOH solution used to adjust the pH value is 0.05-0.2 mol / L;
[0014] In the above steps (2) and (3), the stirring speed of the magnetic stirrer used during magnetic stirring is 500 to 800 rpm, and the stirring time is 4 to 5 hours.
[0015] In the above step (4), the centrifuge speed is 5000-10000 r / min, the water washing times are 3-5 times, and the drying is carried out in an oven at 60-80° C. for 6-8 hours.
[0016] In the process of preparing modified montmorillonite filler, montmorillonite, phytic acid and cerium nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O) is in a weight ratio of (0.15-0.25):(0.7-1.2):(0.8-1.2).
[0017] The modified montmorillonite filler can be further used to prepare a water-based epoxy resin anti-corrosion coating. The water-based epoxy resin anti-corrosion coating is obtained by uniformly mixing the modified montmorillonite filler, deionized water, water-based epoxy resin and curing agent, coating the mixture on the surface of a metal substrate, and curing the mixture to form a film at room temperature. The mass percentage of the modified montmorillonite filler in the coating is 0.1 to 3 wt.%, and the weight ratio of the water-based epoxy resin to the curing agent is (1.5 to 2.5).
[0018] Furthermore, the preparation process of the waterborne epoxy resin anti-corrosion coating is as follows: the waterborne epoxy resin and the modified montmorillonite filler are mixed evenly in proportion, a curing agent is added and stirred evenly, and the mixture is allowed to stand to expel bubbles; the obtained coating slurry is evenly coated on the surface of a 20SiMn steel substrate using a scraper rod, and the coating slurry is left at room temperature for more than 48 hours to completely cure the coating slurry, thereby obtaining the waterborne epoxy resin anti-corrosion coating (WEP / MMT-Ce-PA).
[0019] Furthermore, before the modified montmorillonite filler is mixed with the water-based epoxy resin, the modified montmorillonite filler is first ground, then deionized water is added, and then it is added to the water-based epoxy resin; the metal substrate is first polished to 2000 mesh using sandpaper step by step before coating; the ratio of the modified montmorillonite filler to deionized water is (0.0026~0.076)g:0.1ml.
[0020] The advantages and beneficial effects of the present invention are as follows:
[0021] 1. The modified montmorillonite filler (MMT-Ce-PA) modified by phytic acid and cerium ions involved in the present invention is prepared at a controllable temperature at room temperature, has a simple operation process, and a low price for the synthetic precursor.
[0022] 2. The present invention utilizes two corrosion inhibitors, phytic acid and trivalent cerium ions, to actively protect the corrosion area. In addition, the barrier effect of montmorillonite itself can form synergistic protection with phytic acid and cerium ion corrosion inhibitors, so that the water-based epoxy coating demonstrates superior anti-corrosion properties.
[0023] 3. In 3.5% wt. NaCl solution, compared with the blank control WEP coating, the WEP / MMT-Ce-PA coating of the present invention has higher corrosion resistance and the corrosion current density is also reduced.
[0024] 4. The present invention has simple steps and is easy to operate. The montmorillonite filler loaded with cerium ions and phytic acid functional groups improves the barrier and anti-corrosion performance of the waterborne epoxy coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of the modified montmorillonite in Example 1.
[0026] Figure 2 The EDS spectra of unmodified and modified montmorillonite in Example 1; wherein: (a) unmodified montmorillonite; (b) MMT-Ce filler; (c) MMT-Ce-PA filler.
[0027] Figure 3 Nyquist diagrams of the coatings in Comparative Examples 1-3 and Example 1; wherein (a) is a partial enlarged view of (b).
[0028] Figure 4 The impedance Bode diagrams of the coatings in Comparative Examples 1-3 and Example 1; wherein: (a) Bode impedance modulus diagram; (b) Bode phase angle diagram. DETAILED DESCRIPTION
[0029] The following embodiments are further elaborations of the present invention. It should be understood that the present invention is not limited to the following embodiments, and the methods described in the experimental process are regarded as conventional experimental methods unless otherwise specified. The materials described can be obtained from public commercial channels unless otherwise specified.
[0030] The invention provides a modified montmorillonite filler based on phytic acid and cerium ions and a waterborne epoxy resin anticorrosive coating; the preparation process of the modified montmorillonite filler is: hexahydrated cerium nitrate and phytic acid (PA) solution are added to a montmorillonite dispersion one by one, and a modified montmorillonite filler modified with phytic acid functional groups and cerium ions is obtained by a hydrothermal method.
[0031] Preferably, the amount of phytic acid added to the modified montmorillonite filler during the preparation process is greater than the amount of montmorillonite added to ensure that the montmorillonite is fully reacted.
[0032] Preferably, the montmorillonite is dispersed by ultrasonic dispersion, and the ultrasonic time is 15 to 20 minutes.
[0033] The cerium ions in the modified montmorillonite are derived from cerium nitrate hexahydrate, and the phytic acid functional groups are derived from a PA solution with a concentration of preferably 70 wt.%.
[0034] Preferably, each synthesis reaction time is 4 to 5 hours, and the magnetic stirring speed is in the range of 500 to 800 rpm.
[0035] The waterborne epoxy resin anticorrosive coating is composed of modified montmorillonite filler, waterborne epoxy and curing agent, wherein the mass percentage of the filler is 0.1-3wt.%, and the weight ratio of the waterborne epoxy to the curing agent is preferably 3:2.
[0036] The modified montmorillonite filler, deionized water, water-based epoxy and curing agent are mixed and coated on the surface of the metal substrate, and cured into a film at room temperature to obtain a metal anti-corrosion coating.
[0037] The present invention comprehensively utilizes the chelating ability of phytic acid with metal ions on the surface of the substrate, the deposition protection of cerium ions and anions in the corrosive environment, and the barrier ability of montmorillonite due to its own structural characteristics, and prepares the target filler through a hydrothermal method, thereby realizing a new type of barrier / self-healing water-based epoxy coating - WEP / MMT-Ce-PA.
[0038] The curing agent used in the following examples and comparative examples can be selected from epoxy curing agents such as polyamide 650 / 651.
[0039] Comparative Example 1:
[0040] This example is the preparation of waterborne epoxy coating (WEP coating), the process is as follows:
[0041] Mix 0.1 ml of deionized water, 1.5 g of water-based epoxy resin and 1 g of curing agent, stir for 5 minutes to mix them evenly, and then let them stand for 5 minutes to eliminate bubbles. Then use a scraper to apply the resulting mixture to the surface of a polished and dried 20SiMn steel substrate and let it stand for more than 48 hours at room temperature to obtain a WEP coating.
[0042] Comparative Example 2:
[0043] 0.0026g of unmodified montmorillonite filler was taken, ground and added to 0.1ml of deionized water, then mixed with 1.5g of waterborne epoxy resin and 1g of curing agent and allowed to stand for 5 minutes. The resulting slurry was applied to the surface of a polished and dried 20SiMn steel substrate using a scraper bar and allowed to stand for more than 48 hours at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / MMT coating).
[0044] Comparative Example 3:
[0045] This example is the preparation of WEP / MMT-Ce coating, and the process is as follows:
[0046] 1. Prepare montmorillonite. Take 0.2 g of the montmorillonite and dissolve it in 100 ml of deionized water. First, ultrasonically disperse it for 15 minutes, and then magnetically stir it at room temperature for 2 hours until it is evenly dispersed to obtain a montmorillonite dispersion.
[0047] 2. Add 1.06 g of cerium nitrate hexahydrate to the montmorillonite dispersion obtained in step (1), raise the temperature of the magnetic stirrer to 80° C., and react for 4 hours at 650 rpm to allow the reaction to fully react; obtain the reaction product MMT-Ce.
[0048] 3. The reaction product MMT-Ce obtained in step (2) was centrifuged at 10000 r / min to remove unreacted substances, washed with water three times to obtain a relatively pure MMT-Ce filler; and baked in an oven at 80° C. for 6 h.
[0049] 0.0026g of the above MMT-Ce filler was taken, ground and added to 0.1ml of deionized water, then mixed with 1.5g of waterborne epoxy resin and 1g of curing agent and allowed to stand for 5 minutes. The resulting slurry was applied to the surface of the polished and dried 20SiMn steel substrate using a scraper bar and allowed to stand for more than 48 hours at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / MMT-Ce coating).
[0050] Embodiment 1:
[0051] This example is the preparation of WEP / MMT-Ce-PA coating, and the process is as follows:
[0052] 1. Prepare montmorillonite. Take 0.2 g of the montmorillonite and dissolve it in 100 ml of deionized water. First, ultrasonically disperse it for 15 minutes, and then magnetically stir it at room temperature for 2 hours until it is evenly dispersed to obtain a montmorillonite dispersion.
[0053] 2. Add 1.06 g of cerium nitrate hexahydrate to the montmorillonite dispersion obtained in step (1), raise the temperature of the magnetic stirrer to 80° C., and react at 650 rpm for 4 hours to allow the reaction to be fully completed.
[0054] 3. Add 1 g of 70 wt.% PA solution to the solution obtained in step (2), adjust the pH of the dispersion to 8-8.5 by dropping 0.1 mol / L NaOH solution, and stir the solution at room temperature with a magnetic stirrer (650 rpm) for 4 h until the reaction is complete to obtain an MMT-Ce-PA mixed solution.
[0055] 4. Using a centrifuge at a speed of 10000 r / min to remove unreacted substances in the MMT-Ce-PA mixed solution, washing with water for 3 times to obtain a MMT-Ce-PA mud precipitate; the mud precipitate was baked in an oven at 80° C. for 6 hours to obtain a modified montmorillonite filler (MMT-Ce-PA filler);
[0056] 0.0026g of the above-mentioned MMT-Ce-PA filler was taken, ground and added to 0.1ml of deionized water, then mixed with 1.5g of waterborne epoxy resin and 1g of curing agent and allowed to stand for 5 minutes. The obtained slurry was applied to the surface of the polished and dried 20SiMn steel substrate with a scraper bar and allowed to stand for more than 48h at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / MMT-Ce-PA coating).
[0057] Embodiment 2:
[0058] This example is the preparation of WEP / MMT-Ce-PA coating, and the process is as follows:
[0059] 1. Take 0.15g of montmorillonite and dissolve it in 100ml of deionized water. First, ultrasonically disperse it for 15 minutes, and then magnetically stir it at room temperature for 2h until it is evenly dispersed to obtain MMT dispersion;
[0060] 2. Add 1.2 g of cerium nitrate hexahydrate to the montmorillonite dispersion obtained in step (1), raise the temperature of the magnetic stirrer to 80° C., and react for 4.5 hours at 650 rpm to allow the reaction to fully react; obtain the reaction product MMT-Ce.
[0061] 3. Add 1.2 g of 70 wt.% PA solution to the solution obtained in step (2), adjust the pH of the dispersion to 8-8.5 by dropping 0.1 mol / L NaOH solution, and stir the solution with a magnetic stirrer (650 rpm) at room temperature for 4 h until the reaction is complete to obtain an MMT-Ce-PA mixed solution.
[0062] 4. Use a centrifuge at a speed of 10,000 r / min to remove unreacted substances in the MMT-Ce-PA mixed solution, wash it with water three times, and obtain a MMT-Ce-PA mud precipitate; the mud precipitate is baked in an oven at 80°C for 6 hours to obtain a modified montmorillonite filler (MMT-Ce-PA filler).
[0063] 0.076g of the above-mentioned MMT-Ce-PA filler was taken, ground and added to 0.1ml of deionized water, then mixed with 1.5g of waterborne epoxy resin and 1g of curing agent and allowed to stand for 5 minutes. The obtained slurry was applied to the surface of the polished and dried 20SiMn steel substrate with a scraper bar and allowed to stand for more than 48 hours at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / MMT-Ce-PA coating).
[0064] Embodiment 3:
[0065] This example is the preparation of WEP / MMT-Ce-PA coating, and the process is as follows:
[0066] 1. Take 0.2g of montmorillonite and dissolve it in 100ml of deionized water. First, ultrasonically disperse it for 15 minutes, and then magnetically stir it at room temperature for 2h until it is evenly dispersed to obtain MMT dispersion;
[0067] 2. Add 0.8 g of cerium nitrate hexahydrate to the montmorillonite dispersion obtained in step (1), raise the temperature of the magnetic stirrer to 80° C., and react for 5 hours under stirring at 650 rpm to allow the reaction to fully react; obtain the reaction product MMT-Ce.
[0068] 3. Add 0.7 g of 70 wt.% PA solution to the solution obtained in step (2), adjust the pH of the dispersion to 8-8.5 by dropping 0.1 mol / L NaOH solution, and stir the solution at room temperature with a magnetic stirrer (650 rpm) for 4 h until the reaction is complete to obtain an MMT-Ce-PA mixed solution.
[0069] 4. Use a centrifuge at a speed of 10,000 r / min to remove unreacted substances in the MMT-Ce-PA mixed solution, wash it with water three times, and obtain a MMT-Ce-PA mud precipitate; the mud precipitate is baked in an oven at 80°C for 6 hours to obtain a modified montmorillonite filler (MMT-Ce-PA filler).
[0070] 0.0026g of the above-mentioned MMT-Ce-PA filler was taken, ground and added to 0.1ml of deionized water, then mixed with 1.5g of waterborne epoxy resin and 1g of curing agent and allowed to stand for 5 minutes. The obtained slurry was applied to the surface of the polished and dried 20SiMn steel substrate with a scraper bar and allowed to stand for more than 48h at room temperature to obtain a waterborne epoxy resin anticorrosive coating (WEP / MMT-Ce-PA coating).
[0071] Figure 1 This is the SEM image of the modified montmorillonite in Example 1. It can be seen from the image that the modified montmorillonite presents an irregular flaky structure and a rough surface, indicating that the montmorillonite has been successfully modified.
[0072] Figure 2 The EDS spectra of unmodified montmorillonite, MMT-Ce filler and MMT-Ce-PA filler in Example 1 show that the MMT-Ce-PA filler contains obvious Ce and PA elements, indicating that the two substances are successfully modified.
[0073] Figure 3 Nyquist plots of the coatings of Comparative Examples 1-3 and Example 1; it can be seen that the impedance spectrum radius of the WEP coating in Comparative Example 1 is larger than that of the WEP / MMT coating in Comparative Example 2, but smaller than that of the WEP / MMT-Ce in Comparative Example 3 and the WEP / MMT-Ce-PA coating in Example 1, and the impedance spectrum radius of Example 1 is the largest, indicating that the coating of Example 1 has the best corrosion resistance.
[0074] Figure 4 (a) is the Bode impedance modulus diagram of the coatings of Comparative Examples 1-3 and Example 1, showing that at the lowest frequency, the impedance values of the WEP / MMT-Ce-PA coating, WEP / MMT-Ce coating, WEP coating, and WEP / MMT coating decrease in sequence, and the impedance value of the WEP / MMT-Ce-PA coating of Example 1 is one order of magnitude higher than that of the WEP coating, indicating that adding MMT filler to the waterborne epoxy will reduce the corrosion resistance of the coating, while adding the final modified montmorillonite in the example to the waterborne epoxy coating significantly increases the corrosion resistance of the coating. Figure 4 (b) is the Bode phase angle diagram. According to the relative position in the diagram, the more it moves to the left, the better the corrosion resistance. It can be seen that the corrosion resistance of WEP / MMT-Ce-PA coating is the best.
[0075] In addition, the above tests were performed on the WEP / MMT-Ce-PA coating prepared in Example 2-3. The test results showed that the above-mentioned properties of the WEP / MMT-Ce-PA coating were better than those of the WEP coating and the WEP / MMT-Ce coating.
[0076] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application. The above are only preferred implementations of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A modified montmorillonite filler based on phytic acid and cerium ions, characterized in that: The modified montmorillonite filler is formed by taking montmorillonite as a carrier, and loading phytic acid functional groups and cerium ions on the carrier.
2. The modified montmorillonite filler based on phytic acid and cerium ions according to claim 1, characterized in that: The preparation process of the modified montmorillonite filler (MMT-Ce-PA) comprises the following steps: (1) using montmorillonite as a raw material to prepare a montmorillonite dispersion (MMT dispersion); (2) adding Ce(NO3)3·6H2O to the montmorillonite dispersion in step (1), and reacting completely at a constant temperature of 60 to 80°C and under magnetic stirring; (3) adding a phytic acid (PA) solution having a concentration of 65-75 wt.% to the material obtained after the reaction in step (2), and then gradually adding a NaOH solution to adjust the pH value of the solution to 8-8.5, and stirring with a magnetic stirrer until the reaction is complete to obtain an MMT-Ce-PA mixed solution; (4) using a centrifuge to remove unreacted substances in the MMT-Ce-PA mixed solution, and washing with water to obtain a MMT-Ce-PA mud precipitate; the mud precipitate is dried to obtain the modified montmorillonite filler (MMT-Ce-PA), which is then sealed and stored.
3. The modified montmorillonite filler based on phytic acid and cerium ions according to claim 2, characterized in that: In step (1), the preparation process of the montmorillonite dispersion (MMT dispersion) is as follows: 0.1-1g of montmorillonite (MMT) is uniformly dispersed in 100ml of deionized water by ultrasonic dispersion method, ultrasonic dispersion is performed for 15-20 minutes, and then the montmorillonite dispersion (MMT dispersion) is uniformly dispersed under magnetic stirring conditions, and the magnetic stirring process is stirring at room temperature for 1-3h.
4. The modified montmorillonite filler based on phytic acid and cerium ions according to claim 2, characterized in that: In step (3), the concentration of the NaOH solution used to adjust the pH value is 0.05-0.2 mol / L.
5. The modified montmorillonite filler based on phytic acid and cerium ions according to claim 2, characterized in that: In step (2) and step (3), the stirring speed of the magnetic stirrer used during magnetic stirring is 500-800 rpm, and the stirring time is 4-5 hours; in step (4), the centrifuge speed is 5000-10000 r / min, the number of water washings is 3-5 times, and the drying is performed by baking in an oven at 60-80° C. for 6-8 hours.
6. The modified montmorillonite filler based on phytic acid and cerium ions according to claim 2, characterized in that: In the process of preparing the modified montmorillonite filler, the weight ratio of the used montmorillonite, phytic acid and cerium nitrate hexahydrate (Ce(NO3)3·6H2O) is (0.15-0.25): (0.7-1.2): (0.8-1.2).
7. A water-based epoxy resin anticorrosive coating based on the modified montmorillonite filler according to claim 1, characterized in that: The water-based epoxy resin anti-corrosion coating is obtained by uniformly mixing the modified montmorillonite filler, deionized water, water-based epoxy resin and curing agent, coating the mixture on the surface of a metal substrate, and curing the mixture at room temperature to form a film; the mass percentage of the modified montmorillonite filler in the coating is 0.1 to 3 wt.%, and the weight ratio of the water-based epoxy resin to the curing agent is 3:(1.5 to 2.5).
8. The waterborne epoxy resin anticorrosive coating according to claim 7, characterized in that: The preparation process of the waterborne epoxy resin anti-corrosion coating is as follows: the waterborne epoxy resin and the modified montmorillonite filler are mixed evenly in proportion, a curing agent is added, stirred evenly, and allowed to stand to expel bubbles; the obtained coating slurry is evenly coated on the surface of a 20SiMn steel substrate using a scraper bar, and is left at room temperature for more than 48 hours to completely cure the coating slurry, thereby obtaining the waterborne epoxy resin anti-corrosion coating (WEP / MMT-Ce-PA).
9. The waterborne epoxy resin anticorrosive coating according to claim 8, characterized in that: Before the modified montmorillonite filler is mixed with the waterborne epoxy resin, the modified montmorillonite filler is first ground, then deionized water is added, and then it is added to the waterborne epoxy resin; the metal substrate is first polished to 2000 mesh using sandpaper step by step before coating; the ratio of the modified montmorillonite filler to deionized water is (0.0026-0.076) g: 0.1 ml.
Citation Information
Patent Citations
Environment-friendly coating based on cerium ion in-situ supported montmorillonite filler and preparation method of coating
CN107629636A
Preparation method of tannic acid modified cerium ion modified montmorillonite / waterborne polyurethane
CN113249024A
Preparation method of dual self-repairing waterborne polyurethane anticorrosive material
CN115181492A